Exploring English Teachers’ Strategies in Managing Online Learning through Google Classroom - Ayu, Mutiara; Sari, Fatimah Mulya (Universitas Negeri Makassar, 2021)
This study was conducted to explore strategies used by Englishteachers in delivering online learning through Google Classroom. It was done through a case study in three classes with three English language teachers at a vocational high school. The data were collected by using Â questionnaire, interview, and observation. Then, data collection, data reduction, data display, and conclusion were conducted to analyze the data. The results showed that all three teachers encountered some obstacles in managing their online learning through Google Classroom. Most of the problems came from the students' participation, internet connection, and material delivering. As a result, it encouraged the teachers to seek and implement certain strategies that were appropriate to cope with these problems. They applied several online teaching strategies to solve the problems in managing online learning through Google Classroom, that is, by facilitating students with WhatsApp group to communicate with them, meeting the students who did not have smartphone directly at school, adapting the materials from several Â references, giving assignment in a simple way, encouraging the students with reward and punishment, and coordinating to each homeroom teacher.